CRITICAL DISCOURSE ANALYSIS OF CAKNA DIRI : A MODULE FOR SEXUAL AND REPRODUCTIVE HEALTH EDUCATION FOR MALAYSIAN PARENTS - Mohammed Rasheedan, Ellin; Siti Hazariah, Abdul Hamid; Siti Roshaidai, Mohd Arifin; Haliza, Hasan; Sajaratulnisah, Othman; Norhasmah, Mohd Zain (IIUM Press, 2025)
This Critical Discourse Analysis (CDA) of the Cakna Diri Module explores how the parenting module, developed by Lembaga Penduduk dan Pembangunan Keluarga Negara (LPPKN), reflects and shapes power dynamics, ideologies, and social practices in the context of parenting sexuality in Malaysia. Utilizing Norman Fairclough’s CDA framework, the study examines how language constructs relationships of authority, conveys cultural and religious values, and communicates moral responsibilities related to SRH. The module emphasizes Islamic principles and conservative social norms, particularly regarding gender roles, sexuality, and parental guidance. Through analysis, the study highlights how the module frames issues such as pre-marital sex, boundaries, and family structures, while reinforcing parents' roles as moral gatekeepers. Furthermore, this CDA addresses how the module responds to societal concerns over youth behaviour, engaging with discourses of modernity and cultural identity in Malaysia. This analysis provides valuable input